[PP.08.20] PREVALENCE OF ATHEROSCLEROSIS AND ARTERIAL STIFFNESS IN PATIENTS WITH ARTERIAL HYPERTENSION AND TYPE 2 DIABETES MELLITUS. (September 2017) - Starostina, E.; Troitskaya, E.; Kotovskaya, Y.; Kobalava, Z.
Abstract : Objective: The aim of the study was to assess the degree of atherosclerosis and arterial stiffness in patients with arterial hypertension and type 2 DM. Design and method: The study included 55 patients with HTN and DM (19 (38%) males, mean age 61.6 ± 12.7 years, mean office BP 142.5 ± 25.5/82.7 ± 10.7 mmHg, HR 75.4 ± 10.2 beats/min), GFR 64 ± 18.4 ml/min/1.73m 2, LDL-C 3.4+1.19 mmol/l). All participants previously received antihypertensive medications: ACEIs – 55 (100%), beta-blockers 12 (21.8%), calcium channel blockers 51 (92.7%), thiazide diuretics 35 (63.6%); 4 (7.27%) patients received statins. Target BP values (<140/85 mmHg) were achieved in 29 (52.7%) patients. Carotid-femoral (CF) and carotid-radial (CR) pulse wave velocity were assessed (Sphygmocor, AtCor), cardio-ankle vascular index (CAVI) and ankle-brachial index (ABI) were evaluated (VaSera 1500, Fukuda Denshi). Increased arterial stiffness was defined as an elevation of pulse pressure (PP) > 60 mmHg, PWV >10 m/s, CAVI >9.0, ABI decrease <0.9 was considered as a marker of subclinical atherosclerosis, ABI > 1.3 as a sign of noncompressible arteries. Stiffness gradient was assessed by CF-PVW/CR-PWV ratio, with values >1 indicating the loss of gradient. Results: In our group mean PP values were 61.0 ± 14.3 mmHg;10 (18.1%) patients had elevation of PP > 60 mmHg. Mean CR-PWV was 7.7 ± 1.18 m/s, mean CF-PWV – 10.3 ± 2.0 m/s, increased CF-PWV >10 m/s was noted in 15 (27.2%) patients. Mean stiffness gradient was 1.3+0.37, values of CF-PWV/CR-PWV >1 were found in 51 (92.7%) patients. Mean CAVI was 8.5 ± 1.8, with elevation > 9.0 – in 23 (49%) patients. Mean ABI was 1.03 ± 0.1, ABI decrease < 0.9 was present in 5 (9%), ABI increase >1.3 in 2 (3.6%) patients Conclusions: Markers of arterial stiffness in HTN patients with DM receiving effective antihypertensive treatment in 52.7% of cases are more prevalent than markers of atherosclerosis. The rate of arterial stiffness varies depending on the diagnostic method used. The highest number of patients is diagnosed with arterial stiffness by CAVI measurement, the lowest number by PP, which may reflect the greater sensitivity of PP to antihypertensive therapy. Patients with HTN and DM have an early loss of stiffness gradient from aorta to peripheral arteries.